ENSURING SUSTAINABLE INVESTMENT DEVELOPMENT IN THE TOURISM SERVICES SECTOR THROUGH INNOVATIVE FINANCIAL MECHANISMS: THE CASE OF SURKHANDARYA REGION, UZBEKISTAN (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
This article examines the development of investment attractiveness in the tourism services sector of Surkhandarya region through the integration of tourism and financial mechanisms. Using statistical data from 2020–2024, the study applies analysis, synthesis, and forecasting methods to identify innovative financial tools that can enhance regional tourism competitiveness. Findings indicate that digitalization, public-private partnerships (PPP), and international investment cooperation significantly contribute to the sustainable development of the tourism economy in Uzbekistan.